Integrasi Ilmu Dalam Kurikulum Pesantren: Tinjauan Filsafat Pendidikan Islam Terhadap Praktik Pendidikan - Taufik Dirin Pathin; Muh. Hanif (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The ongoing dichotomy between religious and secular sciences within Islamic education has prompted the need to reconstruct the epistemological paradigm of pesantren education. Traditionally, pesantren have emphasized religious instruction while providing limited attention to empirical sciences. This study aims to analyze the integration of knowledge within pesantren curricula through the lens of Islamic educational philosophy, focusing on the application of tawhidi epistemology as the foundation for unifying knowledge. Employing a qualitative library research approach, this study conducts philosophical analysis on classical and contemporary works, including those of al-Ghazali, al-Attas, and Fazlur Rahman. The findings reveal that pesantren have begun implementing knowledge integration by merging the curricula of the Ministry of Religious Affairs and the Ministry of Education with traditional Islamic curricula, alongside contextual learning approaches rooted in Islamic values. The study implies that repositioning Islamic educational epistemology from a dichotomous to a tawhidi paradigm is crucial to enable pesantren to produce knowledgeable, ethical, and adaptive generations capable of addressing modern challenges